Penguatan Kapasitas Pemasaran Online bagi Pelaku UMKM Pemustaka di Kota Magelang Provinsi Jawa Tengah - Hastjarjo, Sri; Ayu, Aulia Suminar; Haryono, Novita; Arzil, Andrine Prima Afneta; Abisono, Firya Qurratu'ain; Pawito, Pawito; Haryanto, Haryanto; Arifin, Hamid; Kusumawati, Diah (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2025)
This article discusses an online marketing training program for Micro, Small, and Medium Enterprises (MSMEs) who are also library users in Magelang City. The program was part of a community service initiative by Universitas Sebelas Maret in collaboration with the Library and Archives Office of Magelang City. The background of the program is the low level of digital literacy and online marketing skills among MSME actors, which limits their market reach and product competitiveness. The one-day workshop adopted a hands-on practice approach with practical materials, including basic strategies for digital marketing through social media, optimization of Instagram and WhatsApp Business platforms, and the creation of engaging and effective promotional content. A key framework introduced was the "3K" strategy: Know your market, Consistent branding, and Active communication. Evaluation results showed significant improvements in participants’ understanding and skills in digital marketing. Moreover, the training reinforced the role of public libraries as centers of productive literacy, bridging access to information with community economic empowerment. This activity demonstrates that synergy between academic institutions, local government, and MSME communities can foster inclusive training models that are responsive to the real needs of small businesses in the digital era.